2017
DOI: 10.1097/aln.0000000000001725
|View full text |Cite
|
Sign up to set email alerts
|

Extubation Success Prediction in a Multicentric Cohort of Patients with Severe Brain Injury

Abstract: Background Patients with brain injury are at high risk of extubation failure. Methods We conducted a prospective observational cohort study in four intensive care units of three university hospitals. The aim of the study was to create a score that could predict extubation success in patients with brain injury. Results A total of 437 consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 30 publications
3
65
2
5
Order By: Relevance
“…In cases of prolonged diminished levels of consciousness, neurocritical patients may never undergo the weaning process, and tracheostomy is commonly employed in the management of these patients, but the timing of this procedure is controversial. Prolonged invasive mechanical ventilation (IMV) in this category of patients can lead to higher rates of ventilator-acquired pneumonia, increased ICU length of stay, and higher mortality rates [24,25,27] compared with non-neurological critically ill patients [28].…”
Section: Neurocritical Patientsmentioning
confidence: 99%
“…In cases of prolonged diminished levels of consciousness, neurocritical patients may never undergo the weaning process, and tracheostomy is commonly employed in the management of these patients, but the timing of this procedure is controversial. Prolonged invasive mechanical ventilation (IMV) in this category of patients can lead to higher rates of ventilator-acquired pneumonia, increased ICU length of stay, and higher mortality rates [24,25,27] compared with non-neurological critically ill patients [28].…”
Section: Neurocritical Patientsmentioning
confidence: 99%
“…The clinical features and level of arousal compatible with successful extubation are still debated in brain injury patients and, therefore, the rates of extubation failure and delayed extubation remain high in this population. Extubation failure is associated with significant morbidity: nosocomial pneumonia, longer mechanical ventilation duration, increased ICU length of stay and higher mortality [6,10,11], but the cause of extubation failure is probably more deleterious than the failure itself [6]. The fear of extubation failure explains the high rate of delayed extubation in neuro-ICU patients (extubation is considered as delayed when patients are not extubated within 48 h of meeting defined readiness criteria [6]), even though delaying extubation is not a guarantee of success [6].…”
Section: Weaning From Invasive Mechanical Ventilation and Extubationmentioning
confidence: 99%
“…A descriptive monocenter study confirmed that mechanical ventilation discontinuation accounted for 50% of deaths in a population of neurovascular patients (stroke, intracerebral hemorrhage or subarachnoid hemorrhage) [33]. In most studies regarding extubation in brain injury patients, patients undergoing withdrawal of life-sustaining therapies are not included [10,11], but the timing, modalities and consequences of extubation in this context are not addressed in the neuro-ICU literature.…”
Section: Extubation Tracheostomy and Withdrawal Of Lifesustaining Thmentioning
confidence: 99%
See 2 more Smart Citations